Knowledge representation through ontologies: an application in the electronic democracy field - Santos,Paloma Maria (2016)
ABSTRACT Thanks to their potential to facilitate understanding and assist in the characterization of an interest area, ontologies are widely used as tools for knowledge representation. However, in the electronic democracy context, a systematic review found that this practice needs further exploration. Accordingly, this paper aims to develop an ontology in the electronic democracy field. As a result, we achieved a unique and novel knowledge capture in that domain. Such representation, besides pointing out key domain elements, could aid in the development of electronic democracy initiatives and improve web portals.